PANDANGAN BADAN HISAB RUKYAT DAERAH (BHRD) KABUPATEN CIREBON TERHADAP PERUBAHAN KRITERIA MABIMS - Samsudin samsudin; Kusdiyana Kusdiyana; Muhammad Hisyam Bahari (IAIN Syekh Nurjati Cirebon, 2023)
The MABIMS Imkan al-ru'yah criterion is a criterion that has been agreed upon by the countries that are members of the MABIMS section, namely Brunei, Indonesia, Malaysia and Singapore. This criterion is still held by the Indonesian state in determining the beginning of the lunar month. This criterion is used as a guide in rejecting or accepting the results of ru'yah. According to the Cirebon Regency BHRD regarding the change in the MABIMS 2021 criteria, it aims to increase the minimum hilal sighting criteria, especially in the Cirebon district which is one of the national hilal rukyatul points. The Mabims 2021 criteria with a hilal height of 3° and an elongation of 6.4° are expected to be able to increase the possibility of observing the new moon in the regions of MABIMS countries, especially Indonesia.